The Kinematic and Kinetic Development of Sprinting and Countermovement Jump Performance in Boys - Wdowski, Maximilian M.; Noon, Mark; Mundy, Peter D.; Gittoes, Marianne J. R.; Duncan, Michael J. (Frontiers in Bioengineering and Biotechnology, 2020)
Background: The aim of the study was to examine the kinematics and kinetics of sprint running and countermovement jump performance between the ages of 8 to 9, and 11 to 12 year old boys in order to understand the developmental plateau in performance. Methods: 18 physically active boys (Age: 10.1±1.6), in an under 9 years old (U9) and an under 12 years old (U12) group performed 15 m sprints and countermovement jumps. A 3D motion analysis system with synchronized force platforms, collected kinematic and kinetic data during the first stance phase of the sprint run and the countermovement jump. Results: The U12 group had a significantly greater height (U9: 1.364±0.064 m; U12: 1.548±0.046 mm), larger mass (U9: 30.9±3.5 kg; U12: 43.9±5.0 kg), superior sprint performance over 0-5 m (U9: 1.31±0.007 seconds; U12: 1.23±0.009 seconds) and 0-15 m (U9: 3.20±0.17 seconds; U12: 3.01±0.20 seconds), and increased jump height (U9: 0.17±0.06 m; U12: 0.24±0.10 m) than the under 9 group. During the first stance phase of the sprint the U12 group had a significantly greater vertical (U9: 0.22±0.02 BW/s; U12: 0.25±0.03 BW.s) and horizontal impulse (U9: 0.07±0.02 BW/s; U12: 0.09±0.03 BW.s) during than the U9 group. When performing a countermovement jump the U12 group had a significantly greater mean average eccentric force (U9: 407.3±55.0 N; U12: 542.2±65.1 N) and mean average concentric force (U9: 495.8±41.3 N; U12: 684.0±62.1 N). Joint kinematics for the countermovement jump were significantly different between age groups for the ankle range of motion (U9: 80.6±17.4 º; U12: 64.1±9 º) and knee minimum joint angle (U9: -5.7±3.9 º; U12: 0.0±4.4 º). Conclusion: The study demonstrates for the first time that the development of physically active boys between the ages of 8-9 to 11-12 years increased the ground reaction forces and impulses during sprint running and countermovement jumps, but that sprint running technique had not developed during this period. Furthermore, countermovement jump technique was still emerging at the age of 8-9 years old. Practitioners need to implement on-going fine-grained sprint running and CMJ technique sessions to ensure that the increased force producing capabilities that come with age are appropriately utilized.